The Level of Digital Skills for Amman Arab University students in Light of Some Variables - Shogran, Rami Ibrahim AbdelRahman; Al-Nasraween, Mo’en Salman Salim; Al-Taj, Heyam Musa Mustafa; Al-Shboul, Mohannad Khaled Radwan; Bazadough, Dina Said AbdelHamid (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to investigate the level of digital skills among students of Amman Arab University in light of some variables. The study sample consisted of (308) students from various faculties and academic programs, to achieve the goal of the study, a scale for digital skills was applied to the study sample after assuring validity and reliability of it. The study results showed the existence of moderate level of digital skills among the students of Amman Arab University; moreover, the results showed no statistically significant differences between the means of digital skills according to gender, faculty, GPA variables. The results displayed statistically significant differences for the interaction between the faculty and the students’ PGA in favor of students with a "very good" average in scientific faculties. The study recommended developing students ‘digital skills through holding training workshops, scientific lectures and focusing on courses that create and establish appropriate digital skills.